PERSEPSI MASYARAKAT TERHADAP STATUS JANDA CERAI USIA MUDA DI KELURAHAN SUNGAI APIT KECAMATAN SUNGAI APIT KABUPATEN SIAK - Safitri, Irni; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Socially, the general public still views the status of the widow with a negative view. The term widow, regardless of social class is a disgrace. With social burdens imposed, without ever wanting to see the various factors or causes of widowhood, people tend to judge and label bad and cruel to young widows. This study aims to determine the perception of the community of Sungai Apit River to the status of divorce widow of young age and know the factors that cause the perception. In addition, this study is expected to increase knowledge and insight for the community about the status of widows. This research is a quantitative research with descriptive type. Population and Sample of this research is community of Sungai Apit with sampling technique that is Simple Cluster Sampling followed by 94 respondents. Data collection was done by using questionnaire and documentation method. The analysis is done by processing the data into cross tabulation to facilitate the writer to analyze the findings of the field. The conclusion of this research is that public perception on the status of young widow in Sungai Apit Village is not all negative. There are several factors that influence the society on the status of divorced widows young age is a factor of the community, the factor of the young widow, and social environment. Based on the research, the factors of the perception and the social environment are positive, while the negative perception is the factor of the young widow themselves, such as education, divorce, occupation, parenting, and the fulfillment of the need of young widow's family.Keywords: Perception, Status of young widow